2000
DOI: 10.1111/1467-9566.00214
|View full text |Cite
|
Sign up to set email alerts
|

Epistemology, evidence and experience: evidence based health care in the work of Accident Alliances

Abstract: Evidence based health care has attracted considerable interest from NHS commissioners, public health specialists and sociologists as both a rational approach to decision making and as representing an ideological shift in health care. This paper explores the social construction of`evidence' in one arena, that of the work of Accident Alliances. Interviews with key participants and observations of meetings suggest a high level of consensus that evidence was important for their work in terms of strategic decision … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
46
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 15 publications
1
46
0
Order By: Relevance
“…As the authors comment: "Depending on the group dynamics, interventions using such skills could result in a radical shift in the way in which the group made sense of new information, and incorporated it into their thinking, or could lead to a 'stand-off' in which the new information was simply ignored". Judith Green's exploration of local decision-making by multi-professional Accident Alliances came to similar conclusions about the critical role of individuals in the construction and utilisation of evidence by policymaking groups (Green, 2000). She found that the personalised, practical knowledge of key people was frequently more significant than citations of published research evidence about 'what works'.…”
Section: Evidence Policymaking and Discourse: Examples From Empiricamentioning
confidence: 90%
See 1 more Smart Citation
“…As the authors comment: "Depending on the group dynamics, interventions using such skills could result in a radical shift in the way in which the group made sense of new information, and incorporated it into their thinking, or could lead to a 'stand-off' in which the new information was simply ignored". Judith Green's exploration of local decision-making by multi-professional Accident Alliances came to similar conclusions about the critical role of individuals in the construction and utilisation of evidence by policymaking groups (Green, 2000). She found that the personalised, practical knowledge of key people was frequently more significant than citations of published research evidence about 'what works'.…”
Section: Evidence Policymaking and Discourse: Examples From Empiricamentioning
confidence: 90%
“…It acknowledges that there is no principled way of making priority decisions (Holm, 1998) and that evidence cannot 'speak for itself' (Green, 2000). (Klein, 1993) And so this phase of the priority setting debate is characterised by policymakers seeking to strengthen the institutional processes of decisionmaking, and involving not only experts and professionals in decision-making but also the public.…”
Section: Phasementioning
confidence: 99%
“…Stephen Harrison's (1998) political-economic analysis, and Judith Green's (2000) article on 'epistemology, evidence and experience'. Harrison's (1998) view was that while EBHC made sense politically as a vehicle to engage doctors in the rationing of healthcare, it did not make sense philosophically.…”
Section: Philosophical Sociologies Of Ebhcmentioning
confidence: 99%
“…himself in dissent against EBHC, because of its theoretical unsophistication. Green (2000) began her analysis of EBHC with the conceptual construction of Evidence as a route to clinical decision-making. She found that different disciplines and practices generate different evidential cultures which, being constructed in mutual distinction, are incompatible.…”
Section: Philosophical Sociologies Of Ebhcmentioning
confidence: 99%
“…Some of the work I did on looking at how, for instance, evidence was used in what were then called Accident Alliances, multi-sector organisations that were about having a more rational approach to injury prevention (Green, 2000). And it struck me that whenever anyone wanted to make a claim for an evidence-based approach, it never worked in discussion, unless they could tie that to a very emotional appeal.…”
Section: Bob: Do You Think Risk Has Become a Key Element Of Governmenmentioning
confidence: 99%